2017
DOI: 10.1016/j.afjem.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of nurse-led triage at Connaught Hospital, Sierra Leone in the immediate post-Ebola period

Abstract: IntroductionNurse-led triage, using the South African Triage Scale, was introduced to the emergency centre of the tertiary referral hospital in Freetown, Sierra Leone in early 2014 prior to the Ebola epidemic. The aim of this study was to measure the effectiveness of the process now that the country has been declared free of Ebola.MethodsThe study was conducted over a five-day consecutive period in the adult emergency centre of the main government teaching hospital in December 2015. The times from arrival to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In Sierra Leone, the SATS proved a reliable tool that also led to improvements in waiting times for high acuity patients. 13 Similarly, in Somaliland 12 and rural South Africa, 14 the SATS demonstrated feasibility as well as sound predictive validity. A recent review of the SATS in non-African settings found a significant correlation between triage category, admission rate and mortality, similar to the findings in the present study.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In Sierra Leone, the SATS proved a reliable tool that also led to improvements in waiting times for high acuity patients. 13 Similarly, in Somaliland 12 and rural South Africa, 14 the SATS demonstrated feasibility as well as sound predictive validity. A recent review of the SATS in non-African settings found a significant correlation between triage category, admission rate and mortality, similar to the findings in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…The findings of the present study are broadly consistent with the experience of other resource‐limited ED that have recently implemented triage scales. In Sierra Leone, the SATS proved a reliable tool that also led to improvements in waiting times for high acuity patients . Similarly, in Somaliland and rural South Africa, the SATS demonstrated feasibility as well as sound predictive validity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…All patients presenting to the AaBET Hospital emergency department (ED) pass through a single point of triage, where trained emergency triage nurses record essential clinical and demographic information and assign a triage acuity designation according to the South African Triage Scale (SATS) [ 9 ]. The SATS has been validated for use in diverse low-income urban adult and pediatric ED settings, [ 10 13 ] and has high reported inter-rater reliability among emergency nurses (ĸ = 0.92), [ 14 , 15 ] and in trauma settings [ 16 ]. It is currently used in all public EDs in Addis Ababa.…”
Section: Methodsmentioning
confidence: 99%